2017
DOI: 10.1007/s00431-017-3060-3
|View full text |Cite
|
Sign up to set email alerts
|

Soccer helps build strong bones during growth: a systematic review and meta-analysis

Abstract: Soccer may be considered a sport that positively affects bone mass during growth. Pubertal soccer players presented increased bone mass compared to controls or other athletes; however, these bone differences are minimized during the prepubertal stage. What is known: • It has been described that childhood and adolescence are important periods for bone mass and structure. • Previous studies have demonstrated that soccer participation improves bone mass in male and female children and adolescents. What is new: • … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 50 publications
1
22
0
2
Order By: Relevance
“…Football is also a suitable means to improve fitness and health in children. The developing organism is exposed to important stimuli targeting particularly the cardiovascular and the musculoskeletal systems as well as metabolism [ 11 , 12 , 13 ]. Various studies showed that playing football leads to increased physical fitness and considerable health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Football is also a suitable means to improve fitness and health in children. The developing organism is exposed to important stimuli targeting particularly the cardiovascular and the musculoskeletal systems as well as metabolism [ 11 , 12 , 13 ]. Various studies showed that playing football leads to increased physical fitness and considerable health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on impact it has been widely demonstrated that sports that entail high impacts improve bone mass [24][25][26], and those reviews that included a variety of sports always found that athletes involved in high impact sports presented higher bone values when compared to non-impact sports [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of PA and sedentarism have been associated with the onset of different pathologies and health problems [6,7]. Numerous studies have demonstrated that doing regular PA is beneficial for body composition [8][9][10], bone health [11,12], psychological health and stress [13,14], and cardiorespiratory capacity, among others [15][16][17][18]. The prevalence of these illnesses is still increasing, leading to greater morbidity and mortality, and the consequent urgent need to implement effective PA programs to reduce the sedentary behavior of the population [19].…”
Section: Introductionmentioning
confidence: 99%